Socio-Demographic Factors Responsible for Uptake of Intermittent Preventive Treatment and Health Seeking Behaviours for Malaria in Pregnancy among Women of Reproductive Ages in Nigeria - Timothy, Adejoh Attah; Abubakar, Adamu; John-Paul, Ojochenemi Enemali; Zainab, Ibrahim Suleiman; Bashira, Isah; Jeffree, Leleji; Nazir, Ibrahim Bello; Solomon, Jonathan Hussaini; Amina, Emidowojo Umar; Ishaya, Daniel Bwala; Asenetu, Iye Ibrahim; Zainab, Ahmed Al-Gazali; et al. (Journal of Public Health International, 2022)
Introduction Malaria in pregnancy is a serious public health concern that could result in detrimental health outcomes for pregnant women and their foetuses. In Nigeria, there is still a significant risk of the disease epidemic and adverse effects especially in pregnancy. The aim of this study is to assess the socio-demographic factors associated with Intermittent Preventive Treatment and health seeking behaviours for malaria in pregnancy among women of reproductive ages in Nigeria Methods Using the National Demographic Survey (NDHS) 2018 data, a cross sectional study was conducted to assess socio-demographic factors associated with Intermittent Preventive Treatment (IPT) for Malaria among Nigerian women of reproductive ages. Result Majority were between ages 30-39 years (39.5%), married/cohabiting (91.8%), Muslims (59.5%), from the north (68.9%), uneducated ( 49.9%), poor (47.5%), and grand parous (65.7%). 63.4% of the women had taken fansidar for malaria in pregnancy while only 6.1% had received healthcare for malaria from informal sources. Except for marital status, all socio-demographic variables (regions, highest educational level, wealth index, age group, religion and parity) were significantly associated with intake of IPT. Additionally, region, education, wealth index, age group, marital status and religion were associated with health seeking behaviour for malaria in pregnancy (P<.05). After control for other variables, wealth index, highest educational level, married/cohabiting marital status and religion was significantly associated with intake of IPT while region, primary and secondary education, poorer and richest wealth index, widowed/separation influenced health seeking for malaria in pregnancy (P<.05). Conclusion The National Malaria Elimination programme should evaluate existing policies that develop interventions that are centred on high risk population in order to prevent malaria in pregnancy while improving health seeking behaviours of women of reproductive ages.
Keywords: Malaria in pregnancy; intermittent preventive treatment; health seeking behaviour; women.